Regulation and employment: assessing wage elasticity in Indian manufacturing. (2nd January 2017) - Singh, Jitender; Mitra, Arup
ABSTRACT: Is wage 'flexibility' a prerequisite to raise employment, and if so, can wage reduction actually bring a sizable increase in employment? These are the two important and related questions that this paper deals with. Based on the panel data (time-series, cross-section-pooled) across various groups of industries over the time period, 2008–2009 to 2011–2012, the paper estimates for the organized/formal manufacturing sector in India the relationship between wage and employment, and the correspondence between income share of labour and growth in employment. The statistically weak relationship between wage and employment, estimated econometrically in terms of wage elasticity of employment, may be taken to suggest that deregulation perceived through wage flexibility cannot raise employment. In addition, the wage share of workers in gross value added has already attained a low magnitude, along with its skewed distribution towards the low end. Hence, the argument for introducing flexibility in wage and hiring and firing practices to facilitate labour cost adjustments and raise employment does not seem be an effective policy option. Rather, other initiatives related to skill formation and infrastructural investment, encouraging industrial expansion, need to be pursued.